Protest Songs From Indonesia And Australia: A Musicological Comparison - Kiernan Box; Greg Aronson (Journal of Urban Society's Arts, 2022)
Protest music is both commercially viable and an important tool for shaping community awareness of socio-political issues. Indonesian and Australian artists have produced protest music which has stimulated significant effect upon community attitudes and behaviours. Socio-political issues can be described and examined in songs using various lyrical methods, including strategic use of characters and narrative. Iwan Fals is a Javanese singer-songwriter who frequently employs satire and parody in relation to weighty political issues. Cold Chisel, Midnight Oil and Paul Kelly are Australian rock artists who have used real-life events as the inspiration for protest songs, many of which are delivered with a confrontational mode of lyric and performance. Compared to Australian acts, Indonesian artists have faced greater risk to personal freedom by engaging in protest music; this may explain why Indonesian protest songs are often presented with more subtle characteristics. from the abstract or from the body of the text, or from the thesaurus of the discipline. Lagu Protes dari Indonesia dan Australia: Perbandingan Musikologi. Musik protes layak secara komersial dan peranti penting untuk membentuk kesadaran masyarakat tentang masalah sosial-politik. Seniman Indonesia dan Australia telah menghasilkan musik protes yang memberikan pengaruh signifikan terhadap sikap dan perilaku masyarakat. Isu sosial-politik dapat dideskripsikan dan dikaji dalam lagu dengan menggunakan berbagai metode lirik, termasuk penggunaan karakter dan narasi yang strategis. Iwan Fals adalah penyanyi-penulis lagu Jawa yang sering menggunakan sindiran dan parodi terkait dengan isu-isu politik yang berat. Cold Chisel, Midnight Oil, dan Paul Kelly adalah artis rock Australia yang telah menggunakan peristiwa kehidupan nyata sebagai inspirasi untuk lagu-lagu protes, banyak di antaranya dibawakan dengan gaya lirik dan penampilan yang konfrontatif. Dibandingkan dengan artis Australia, artis Indonesia menghadapi risiko yang lebih besar terhadap kebebasan pribadi dengan terlibat dalam musik protes; ini mungkin menjelaskan mengapa lagu-lagu protes Indonesia seringkali disajikan dengan ciri-ciri yang lebih halus. dari abstrak atau dari tubuh teks, atau dari tesaurus disiplin.